SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI CALON KEPALA PUSKESMAS MENGUNAKAN METODE MULTI ATTRIBUTE UTILITY THEORY (MAUT) (STUDI KASUS: PUSKESMAS DESA LAMA SEI LEPAN) - Jamillah Nasution; Muhammad Syahrizal (STMIK Budi Darma, 2019)
Desa Lama Health Center is a community health service center for first aid for local communities who want to seek treatment or consult about their health, which serves all public health problems in the fields of childbirth, treatment, outpatient care, hospitalization, baby posyandu and so forth. Decision Supporter. The problems faced by the Old Village Health Center are still using manual methods, especially in determining the recommendation of candidates for Head of the Health Center. On this occasion the authors propose to make decisions for the selection of candidates for the head of the puskesmas using Microsoft Visual Studio 2008. From the results of prospective head centers using the Decision Support System by using the multi attribute utility theory(MAUT) method to facilitate employed in datermining the best decisions in Puskesmas Desa Lama Sei Lepan.Keywords: SPK Recommendation of Candidate Head of Puskesmas, MAUT